Jam-a is highly expressed on human hematopoietic repopulating cells and associates with the key hematopoietic chemokine receptor cxcr4. - Watt, S; Chang, C; Hale, S; Cox, C; Blair, A; Kronsteiner, B; Grabowska, R; Zhang, Y; Cook, D; Khoo, C; Schrader, J; Buglass Kabuga, S; et al. (Wiley, 2016)
Hematopoietic stem/progenitor cells (HSPCs) reside in specialized bone marrow microenvironmental niches, with vascular elements (endothelial/mesenchymal stromal cells) and CXCR4-CXCL12 interactions playing particularly important roles for HSPC entry, retention and maintenance. The functional effects of CXCL12 are dependent on its local concentration and rely on complex HSPC-niche interactions. Two Junctional Adhesion Molecule family proteins, JAM-B and JAM-C, are reported to mediate HSPC-stromal cell interactions, which in turn regulate CXCL12 production by mesenchymal stromal cells (MSCs). Here, we demonstrate that another JAM family member, JAM-A, is most highly expressed on human hematopoietic stem cells with in vivo repopulating activity (p<0.01 for JAM-Ahigh compared to JAM-AInt or Low cord blood CD34+ cells). JAM-A blockade, silencing and overexpression show that JAM-A contributes significantly (p<0.05) to the adhesion of human HSPCs to IL-1β activated human bone marrow sinusoidal endothelium. Further studies highlight a novel association of JAM-A with CXCR4, with these molecules moving to the leading edge of the cell upon presentation with CXCL12 (p<0.05 compared to no CXCL12). Therefore, we hypothesize that JAM family members differentially regulate CXCR4 function and CXCL12 secretion in the bone marrow niche.